Local Public Finance in the Philippines: In Search of Autonomy with Accountability - Rosario G. Manasan (Philippine Institute for Development Studies (PIDS), 2004)
Twelve years into the implementation of the Local Government Code of 1991, it is but opportune to assess how the key features of this landmark legislation has contributed to (or detracted from) achieving the balance between local autonomy and accountability. The literature on fiscal decentralization suggests that these two goals are not incompatible. In fact, real autonomy (in the sense of subnational governments being able to link their spending decisions with their revenue/tax decisions) promotes fiscal responsibility. In the context of the ongoing debate in the Philippines, however, local autonomy has been equated (by many LGUs officials) with the independence of LGUs from central government interference. As such, LGU officials have focused more on securing even higher levels of block grants in order to address the widely perceived vertical fiscal imbalance. However, closer scrutiny of the problem indicates that greater tax decentralization coupled with a well designed intergovernmental transfer system that includes elements of fiscal equalization and categorical grants conditional on the achievement of minimum service standards would better enhance the gains that are forthcoming from the decentralization process while minimizing the risks of macroinstability.
Keywords: 330; fiscal decentralization; fiscal autonomy; fiscal accountability; tax assignment; expenditure assignment; vertical balance; horizontal balance; block grants; categorical grants; equalization grants; Finanzpolitik; Finanzreform; Dezentralisierung; Finanzbeziehungen; Philippinen